2013
DOI: 10.1097/prs.0b013e31827c6e2e
|View full text |Cite
|
Sign up to set email alerts
|

Transdiaphragmatic Omental Harvest

Abstract: Transdiaphragmatic omental harvest provides safe and efficient coverage of deep sternal wounds without a laparotomy incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…de Kraker, et al demonstrated that grip and pinch strength are significantly lower in severe RLD compared with mild RLD [3]. Our data support these findings, as the hands that had poor S-D outcome were the ones with an absent radius or preoperative abnormalities of the pollicized digit.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…de Kraker, et al demonstrated that grip and pinch strength are significantly lower in severe RLD compared with mild RLD [3]. Our data support these findings, as the hands that had poor S-D outcome were the ones with an absent radius or preoperative abnormalities of the pollicized digit.…”
Section: Discussionsupporting
confidence: 87%
“…They found positive outcomes in two JHFT subtests (page turning and checker stacking) as well as patient/parent assessments of thumb appearance and function, despite poor strength and performance on the pegboard test. De Kraker, et al studied pollicized thumb range of motion, strength, sensation, and satisfaction in a series of 40 patients ages 5–25 years [3]. They also found high patient and parent satisfaction with surgical outcome despite diminished strength and range of motion, especially for interphalangeal and metacarpophalangeal extension and interphalangeal flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies of outcomes after early childhood finger pollicization for thumb hypoplasia have demonstrated decreased strength and performance on functional tests compared to age-matched norms and non-operated contralateral hands 21-25 . Despite their functional limitations, patients and parents tend to rate their satisfaction and quality of life unexpectedly high 26-29 .…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, short courses of antimicrobial prophylaxis are preferred over longer courses to reduce costs, drug additional surgical trauma and late flap-related morbidity such as muscular weakness, pain, and hernias [86] . An alternative plastic procedure to pectoralis muscle flaps is the use of omentum that promotes significant angiogenesis, immunologic function, and antimicrobial activity supporting tissue-generation promotion with great capacity to occupy dead space [6,87,88] . Usually, the use of omentum is considered in the case of complex wounds or when the defect is extremely wide with significant sternal loss.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%